Quantifying spatio-temporal changes in the ecological environment quality and their implications for surface mass movement after a high-magnitude earthquake - Ming Chen; Chuan Tang; Yu Yang; Jiang Xiong (Global Ecology and Conservation)
The accurate detection and assessment of changes in the quality of the ecological environment is crucial under seismic disturbances for regional ecological environment recovery and protection. To ensure ecological safety and reduce the geo-ecological risks in the Wenchuan earthquake-affected areas, assessing the quality of the ecological environment and its underlying influencing factors is an important initiative. First, we developed the multi-temporal remote sensing ecological quality (RSEI) dataset spanning from 2007 to 2023 in the Wenchuan earthquake-affected area. Subsequently, we quantitatively assessed the spatio-temporal evolution of the ecosystem quality based on eight RSEI maps. Meanwhile, we examined the control of elevation, slope, aspect, and gully density on the spatiotemporal variation in RSEI. Finally, we explored the interactions between ecological quality and surface mass movement. We found that the average RSEI decreased from 0.80 before the earthquake to 0.47 after the earthquake, and increased to 0.66 after the 15-year recovery period, which indicates a gradual increase in the general ecological quality from 2008 to 2023. In 2023, 36.2 % of the area will still be below the good level of RSEI. Areas with higher elevations, steeper slopes, SE orientation or higher gully densities have lower ecological resilience. We also found that the susceptibility to surface mass movements such as debris flows and landslides was higher in catchments with poorer ecological quality. Generally, the RSEI oscillatory increasing trend was observed after the 2008 Wenchuan earthquake. If RSEI follows the fitted trend, ecological quality will recover to pre-earthquake levels in 2035. Our study will contribute important information and decision-making references for policymakers to carry out more targeted environmental protection, ecological recovery, and sustainable development efforts.